Pengaruh Lingkungan Kerja dan Keterlibatan Pegawai terhadap Kinerja Pegawai pada Dispora Provinsi Jambi - Rida Meriyanti; Sumarni Sumarni; Dwi Kurniawan (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to determine the effect of the work environment and employee engagement on employee performance at the Youth and Sports Office (Dispora) of Jambi Province. The research method used is descriptive quantitative, with data collected through questionnaires. The study sample consisted of 94 respondents determined using the Slovin formula. Data analysis was conducted using multiple regression analysis, t-test, F-test, and the coefficient of determination (R²). Data processing in this study utilized the SPSS software program. The results of the study indicate that partially, the work environment has a positive and significant effect on employee performance, and employee engagement also has a positive and significant effect on employee performance. Simultaneously, the work environment and employee engagement together have a positive and significant effect on employee performance. Based on these findings, it is recommended that the agency pay attention to the neatness of work results, improve lighting conditions in the workplace, and enhance employee diligence through motivation and rewards.